ANALISIS DEGRADASI DAN DEPRESIASI SUMBERDAYA IKAN BAWIS (Siganus canaliculatus) DI PERAIRAN KOTA BONTANG - Nurul Ovia Oktawati; Qoriah Saleha; Oon Darmasyah (Universitas Lambung Mangkurat, 2019)
Bawis fish that is an endemic species and living in the seagrass biota has been found many in marine water of Bontang city. The activity of catching on this fishes has been worked by fishermen who were staying in Bontang city. Hence, if, the catching activity on this fishes without control in the entire year, it will be predicted overfishing and decreasing resources. The aim of this research was to determine the degradation rate and depreciation rate of Bawis fishes’ resources in Marine water of Bontang city. The data were collected with interview method and questionnaire to the splint and nets fishermen, and stakeholder, as well as from the capture fisheries division of DKP3 institution in Bontang city for collecting of data of time series. The results showed that Bawis fishes’ resources in Bontang city were in degradation and depreciation indicated since 2013. It has been showed by the standard coefficient value was 0.59 and 0.64 more than 0.5 in 2013, further, in 2016 increased to 0.619 and 0.68 respectively. The values of increasing were each more than 0.5, it means that Bawis fishes’ resources in Bontang city were in degradation and depreciation.